COUNTER-CLOCKWISE ROTATION OF THE EASTERN PART OF THE MONGOLIA BLOCK: EARLY CRETACEOUS PALAEOMAGNETIC RESULTS FROM BIKIN, FAR EASTERN RUSSIA - Otofuji Y.-I.; Takaba K.; Takemoto K.; Narumoto K.; Zaman H.; Miura D.; Inokuchi H.; Kulinich R.G.; Zimin P.S.; Sakhno V.G. (My University, 2006)
We present palaeomagnetic results from Lower Cretaceous rocks in Bikin area of the Alchan basin (46.5°N, 134.7°E), Sikhote Alin orogenic belt, Far Eastern Russia. A high-temperature magnetization component with maximum unblocking temperatures at about 590°C was isolated from six sites of dacite welded tuffs in the Albian Alchanskaya Formation. The fold tests for these six sites are positive, suggesting that primary magnetization is preserved in the studied rocks. The tilt-corrected mean direction of D = 309.3°, I = 68.7° (α95 = 10.1°), with a corresponding palaeopole position at 57.0°N, 76.8°E (A95 = 15.1°), indicates a counter-clockwise (CCW) rotation for the studied area. CCW rotation is also indicated from west-directed declinations (D = 249.1°, I = 64.1°, α95 = 11.2°) obtained from secondary magnetization of the Berriasian Kultukha Formation. Combining with the previously reported studies, the westdirected Cretaceous palaeomagnetic directions cover widely the eastern part of the Mongolia block. Comparison with 100 Ma palaeomagnetic pole for Eurasia shows that the eastern part of the Mongolia block experienced a CCW rotation of over 36° with respect to the Eurasian continent later than Late Cretaceous. This rotation is ascribed to post-Late Cretaceous extension that affected the continental basins (the Middle Amur, Sanjiang, Razdolnian, Amur-Zeya and Songliao basins) of the northeast Chinese Plain along the eastern margin of the Mongolia block. Contemporaneous with this CCW rotation, similar extension resulted in clockwise rotation of the eastern part of the North China block. © 2005 The Authors Journal compilation © 2005 RAS.
Keywords: CONTINENT; CRETACEOUS; DEFORMATION; MONGOLIA BLOCK; PALAEOMAGNETISM; TECTONICS; Mesozoic::Cretaceous; Мезозой::Меловая